DIGITAL ACTIVISM: THE CASE STUDY OF INTERNET USERS’ REACTION TO THE NEW EU COPYRIGHT RULES - Nećak, Mirjana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2020)
Social digital activism is a topic less addressed by the scientific community. Following explanations of digital activism and its manifestations, this paper presents and analyzes the case of reactions of Internet users to the proposal to amend the European Union Copyright Directive. The emphasis is on digital activism that animates average Internet users, members of virtual communities which are inherently non-political. Through the case study, the elements of digital activism are evident: dissemination of information, meta-advertising, assertion, digital petitions, flood method. This paper emphasizes the importance of digital activism, its advantages, and its disadvantages. By observing the events that followed the reactions of Internet users to Article 17 in the proposal for a new EU Copyright Directive from 2016 until its adoption and later on, we gain insight into the need to combine online and offline activism.